Brukermedvirkning i psykiatriske institusjoner. Praktisering av "brukermedvirkning" gjennom miljøterapeutiske aktiviteter - Vår Mathisen; Aud Obstfelder; Geir Lorem; Per Måseide (Septentrio Academic Publishing, 2015)
The purpose of this article is to examine how user participation is enabled in practice. Fieldwork is conducted in three Norwegian District Psychiatric Centres (DPCs), with an emphasis on observations of staff working with patients and interviews. The theoretical framework is interactionism. The data analysis shows that efforts to involve patients in activities related to their own illness and their stay at the centres are integrated into the work. The findings show that much time is spent on motivating patients to want to live. Practicing of user participation in combination with milieu therapy creates dilemmas. The staff must balance between the various considerations in their work: to motivate individual patients to live and to ensure that daily routines and milieu therapeutic joint activities are implemented. Such dilemmas give the staff a feeling of inadequacy in the practice of user participation. Because, either they must pressure patients to do things against their will or reject individual wishes for adapted services to get the daily routines to go round.